The Current Role of Dual Mobility Articulations in Total Hip Arthroplasty - Silverberg, Arnold; Parvataneni, Hari K.; Pulido, Luis; Prieto, Hernan (The Journal of Hip Surgery, 2018)
The concept of dual mobility (DM) bearings in total hip arthroplasty was first introduced by Professors Gilles Bousquet and Andre Rambert in France in 1974 with the goal of enhancing hip stability. Although DM did not receive U.S. Food and Drug Administration approval for commercial use in the United States until 2009, there has been a surge in popularity of DM implants over the past several years, evidenced by the American Joint Replacement Registry data. The enthusiasm for DM stems from a growing body of literature that supports its use across a range of patient populations, most notably revision hip arthroplasty and high-risk primary scenarios. DM has been shown to effectively reduce the risk of dislocation while also exhibiting excellent survivorship. DM does incur some unique risks, namely, intraprosthetic dissociation, but many of the early concerns with DM have not been realized in the literature and do not seem to negatively impact its long-term survivorship. The exact indications for DM have yet to be defined and remain a matter of debate. It should be considered as an alternative for any primary or revision hip arthroplasty at high risk for postoperative instability. In this article, the authors review the current literature regarding the clinical success of DM implants for a variety of indications, all of which predispose to hip instability. The history, basic biomechanics, modern designs, and unique complications are also discussed.
Keywords: hip arthroplasty; revision hip arthroplasty; dual mobility cups